Strategi Pengembangan Beras Aruk Pada Kelompok Wanita Tani Maju di Kabupaten Bangka - Eni Karsiningsih; Muhammad Soleh Rafsanjani; Putri Rizki Amelia (Universitas Islam Kadiri, 2022)
This study aims to analyze the aruk rice development strategy carried out by Kelompok Wanita Tani (KWT) Maju. The research method used is the case study method. The sampling technique was carried out by census, by making all members of the Women Farmers Advanced Group as respondents. The number of respondents is 16 people. Data were analyzed using IFAS and EFAS matrix analysis methods and SWOT analysis. The results showed that the aruk rice business matrix I, which was an aggressive strategy. Aruk rice business development strategies are to increase production by optimizing the application of technology, optimizing aruk rice processing technology to maximize product and ensure quality so that it can compete, maintain the uniqueness and quality of aruk rice and expand marketing network, increase promotion and socialization activities for aruk rice so as to increase sales. , increase cassava production and productivity so that the availability of raw materials remains continuous in terms of quality and quantity, establish good partnerships with business actors and the government by increasing the knowledge and skills of members, and improve the management of aruk rice business so that it is better and more efficient in producing processed food. from aruk rice.